Hailstones and halibut bones; adventures in color. - O'Neill, Mary Le Duc, 1908-; Weisgard, Leonard, 1916- (Garden City, N.Y., Doubleday, 1961)
With a sense of rhythm and images, the author explores the spectrum in twelve poems about different colors.
Verse.
Children's Catalog (Wilson)
*LJ*
Horn Book Magazine
3.2
3-6
Keywords: Children's poetry, American; Color -- Juvenile poetry; Color -- Poetry